Evaluation of anhydrous processing and storage methods of the temperate bacteriophage ɸV10 for integration into foodborne pathogen detection methodologies. - Andrew Kanach; Theresa Bottorff; Min Zhao; Jun Wang; George T C Chiu; Bruce Applegate (PLoS ONE)
Due to the nascency of bacteriophage-based pathogen detection technologies, several practical hurdles stand in the way between providing promising proof-of-concept data and development of robust detection platforms. One such hurdle, and the focus of this work, is the development of methods for transitioning laboratory stocks of bacteriophage into functional, consistent, and shelf-stable delivery methods in commercial detection kits. Research described here was undertaken to evaluate two methods for their ability to store the bacteriophage ɸV10 at ambient temperature without aqueous storage solutions while limiting loss of viability. ɸV10 is a temperate bacteriophage which solely infects the zero-tolerance food adulterant Escherichia coli O157:H7 and has been genetically modified to generate a detectable phenotype in host cells. In order to integrate this reporter bacteriophage into food-borne pathogen detection methodologies, two methods of processing phage suspensions for long-term, ambient storage were evaluated: printing solutions onto pieces of dissolvable paper and lyophilizing suspensions with sucrose. Applying phage to dissolvable paper yielded key attributes to consider when addressing phage viability, however, optimized methodology still resulted in an approximate five-log reduction in titer of viable phage. Lyophilization of ɸV10 with various concentrations of the cryoprotectant molecule, sucrose, yielded losses of approximately 0.3-log after 120 days of storage at 23°C. Liquid storage buffer samples with and without sucrose saw a reduction of viable phage of at least 3.9-log in the same period. Additionally, the ability for ɸV10 to form lysogens in an E. coli O157:H7 host was not negatively affected by lyophilization. Drying ɸV10 at ambient temperature drastically reduces the viability of the phage. However, lyophilizing ɸV10 in the presence of sucrose is an effective method for dehydration and storage of the phage in ambient environmental conditions for an extended time lending to commercial application and integration into foodborne pathogen detection methodologies.